A Monoclonal Antibody to the Human Platelet Glycoprotein II b/III a Complex Induces Platelet Activation - Modderman, Piet W; Huisman, Han G; Mourik, Jan A van; Borne, Albert E G Kr von dem (Thrombosis and Haemostasis, 1988)
The platelet glycoprotein (GP) IIb/IIIa complex functions as the receptor for fibrinogen on activated platelets. The effects of two anti-GPIIb/IIIa monoclonal antibodies on platelet function were studied. These antibodies, 6C9 and C17, recognized different epitopes, which were exclusively present on the undissociated GPIIb/IIIa complex. Whereas C17 inhibited the binding of fibrinogen to platelets and platelet aggregation induced by adenosine diphosphate (ADP) or collagen, 6C9 caused irreversible aggregation of platelets, both in the presence and absence of extracellular fibrinogen. When incubated with unstirred (nonaggregating) platelets, 6C9 induced release of alpha and dense granule-constituents as well as binding of 125I-fibrinogen to platelets. The latter was evidently mediated in part by platelet-derived ADP, since it was inhibited to a large extent by apyrase, the ADP-hydrolyzing enzyme. F(ab’)2 fragments of 6C9 did not induce platelet-release reactions but caused (slow) aggregation of platelets in the presence of extracellular fibrinogen.These results indicate that binding of an antibody to a specific site on the platelet GPIIb/IIIa complex may cause fibrinogen-mediated aggregation. The Fc part of the platelet-bound antibody appears to be involved in the induction of platelet release.
Keywords: Platelet activation; Glycoprotein IIb/IIIa complex; Anti-GPIIb/IIIa monoclonal antibody